ANALISIS KESALAHAN KONSEP MAHASISWA PADA PERKULIAHAN KONSEP DASAR MATEMATIKA - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study analyzes conceptual errors in the Basic Concepts of Mathematics course by STIT Al-Hilal Sigli students in the PGMI study program. The purpose of this study was to determine the mathematical concept errors that occurred during lectures. The samples in this study were students of the third semester of PGMI study program who were taking the basic concepts of mathematics course, totaling 73 students consisting of unit I, unit II, and unit III. Data collection techniques are carried out by monitoring each answer from exercises, quizzes, assignments, and student UTS answers. The data analysis technique was carried out by descriptive analysis of students' misconceptions about mathematical concepts. The results of the study found several conceptual errors that occurred, including: (1) conceptual errors in arithmetic operations involving negative numbers, (2) conceptual errors in fractional operations, (3) algebraic concept errors, especially those involving one or two variables, and (4 ) does not complete the units for area and length.